CR-Iterative Process for Asymptotically Quasi- Nonexpansive Mappings - Ritika (International Journal of Mathematics And its Applications, 2017)
In this paper strong convergence theorems for CR-iterative process for asymptotically quasi-nonexpansive mappings are established in the framework of CAT(0) spaces.